Some Issues of Legal Regulations of Employee Share Ownership in the Republic of Armenia - Soghomonyan, Ashkhen (Bulletin of Yerevan University C: Jurisprudence, 2024)
The institution of rewarding employees with company shares in exchange for work is a fairly common tool that provides an opportunity to incentivize employees and prevent labor outflow, which, in turn, can indirectly prevent professional emigration from Armenia. Some manifestations of the legal institution of employee stock ownership have found their place in the RA Law “On Joint-Stock Companies”. Recently, certain changes have been made to the legislation, but they do not fully comply with accepted international practice, are sporadic in nature, do not contain effective mechanisms for protecting the rights of employees using these programs, in addition, the practical possibility of using such programs by companies engaged in certain areas of activity has not been taken into account. Within the framework of the article, an attempt was made to identify the impact of all the mentioned shortcomings on the possibility of practical application of this institute, and also substantiated the importance of such programs in the process of operation of startup companies.Taking into account the analysis carried out in the article, a number of generalizations and practical proposals are made that can help ensure the practical application of this institute.
Keywords: Joint stock company; employee stock ownership; employee stock ownership plan; derivative financial instruments; stock options; phantom stock; startup company